Effects of Newcastle disease virus infection on cisplatin-resistant breast cancer cell line - Jamal, Mohd Hafifi (2015)
Cancer recurrence has been a major problem due to failure of primary treatment such as chemotherapy. Over time, decrease of efficacy in killing tumors by drugs such as cisplatin signals, the need for a new alternative cancer treatment. Oncolytic effects of Newcastle disease virus (NDV) has been demonstrated on a wide spectrum of cancers; thus making it an ideal option to fight chemoresistant cancers. As the whole mechanisms of resistant are still being studied, survivin has been identified as one of the proteins that involve in prolonging the survival of cancer cells during chemotherapy treatment. This study will provide an insight into NDV infection on cisplatin-resistant MCF7 and its correlation with survivin expression. To investigate the oncolytic efficacy of a local strain of NDV strain AF2240 in cisplatin-resistant cancer cells, cisplatin-resistant cell line (MCF7-CR) was established from the MCF7 human breast adenocarcinoma cell line. Both cells were infected with NDV and cell viability was determined by using flow cytometry. Viral proteins and survivin expression throughout infection period was probed and production of virus progeny was assessed by using plaque assay technique. Infection of a mass population of the MCF7-CR with NDV resulted in 50% killing in the first 12 hours post-infection (hpi), comparable to the parental MCF7. From 12 hpi onwards, the remaining MCF7-CR became less susceptible to NDV killing. This reduced susceptibility led to increased viral protein synthesis and virus progeny production. The reduction was also associated with a prolonged cell survival via stabilization of the survivin protein. The findings showed for the first time, the involvement of survivin in the reduction of NDV-induced oncolysis in a subpopulation of cisplatin-resistant cells. The outcome of this research will give a new insight in relationship between NDV, chemoresistant cancer and survivin; allowing researcher to exploit the information to establish a new alternative treatment with better efficacy.